The Influence of Family Leadership Style in Encouraging Awareness and Action on Household Waste Management - Dinda Tri Pangesti; Nurhasan Syah; Indang Dewata; Eri arlian; Muhamad Sholichin (Jurnal Penelitian Pendidikan IPA, 2024)
Family leadership style has an important role in encouraging concrete action regarding household waste management. Parents or heads of households who set a good example and provide active encouragement to family members to participate in environmentally friendly waste management practices can form positive and sustainable habits in the household environment. Thus, it is hoped that this research can make a significant contribution to the role of families in encouraging concrete actions related to household waste management. This research aims to analyze the role of family leadership style in encouraging awareness and action regarding household waste management in a community in Padang City. This research uses a quantitative approach with a causal associative type of research. The sampling method used was a saturated sample, with 63 participants from the local community. The data obtained was described, then a description of the research results was carried out using the TCR technique. The determination analysis technique uses simple linear regression to test the extent of the causal influence between variable (X) on the resulting variable (Y). The research results show that the family leadership style among the community is considered very good, with the respondent's achievement level reaching 90.66%. Meanwhile, awareness and action regarding household waste management is also considered high, with the respondent's achievement level reaching 92.11%. The family leadership style variable was proven to have an influence of 28.4% on community awareness and action regarding household waste management, while the rest was influenced by other factors such as motivation, education level and other environmental factors.